(untitled) (University of Khartoum Engineering Journal, 2022)
Spatially-referenced and up-to-date information system is one of the most useful tools for effectivewastewater planning, management and environmental protection. Therefore, it is necessary to have a system whichprovides facilities through geo-spatial relationships. The River Nile catchment is one of the most importantwatersheds in the Sudan in terms of providing for domestic, agricultural, and industrial purposes and for electricitygeneration. Thus, protection of this important water source is crucial in national development. But, only very fewpoint source treatment plants are currently in operation and non-point source treatment plants are required to beestablished to protect the catchment from pollution. Locating wastewater treatment systems is one of the essentialcomponents, and that needs spatially-oriented data gathering, analyzing and visualizing. Further, GIS-BASEDdecision support systems for available treatment plants are well suited for informing improved analysis andunderstanding of the problems of available treatment plants to perform a reliability to improve analysis andunderstand of the existing situation to choose the appropriate location of treatment through a GIS MODEL BASEusing ARCGIS. This study-plan solve the issues and undertaken logics of GIS to identify the critical socio-economic and environmental factors, and find a more comprehensive and convenient way to optimize the locationsfor wastewater treatment facilities that are suitable for different local conditions in Karary.